2022
DOI: 10.3390/insects13111046
|View full text |Cite
|
Sign up to set email alerts
|

Reference Genes for Expression Analysis Using RT-qPCR in Cnaphalocrocis medinalis (Lepidoptera: Pyralidae)

Abstract: Cnaphalocrocis medinalis is a destructive migratory rice pest. Although many studies have investigated its behavioral and physiological responses to environmental changes and migration-inducing factors, little is known about its molecular mechanisms. This study was conducted to select suitable RT-qPCR reference genes to facilitate future gene expression studies. Here, thirteen candidate housekeeping genes (EF1α, AK, EF1β, GAPDH, PGK, RPL13, RPL18, RPS3, 18S rRNA, TBP1, TBP2, ACT, and UCCR) were selected to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…However, this topic has yet to get much attention, and its significance does not seem adequately understood. Because the option of reference genes varies drastically, insects of the same species, in terms of insect morphology, developmental stage, temperature, sex, and diet conditions, suggest that there is also no absolute generality between benchmark genes for the same species [ 29 , 30 , 31 , 32 ] . For instance, PGK and RPL13 are acceptable internal housekeeping genes in Cnaphalocrocis medinalis under different sexes [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this topic has yet to get much attention, and its significance does not seem adequately understood. Because the option of reference genes varies drastically, insects of the same species, in terms of insect morphology, developmental stage, temperature, sex, and diet conditions, suggest that there is also no absolute generality between benchmark genes for the same species [ 29 , 30 , 31 , 32 ] . For instance, PGK and RPL13 are acceptable internal housekeeping genes in Cnaphalocrocis medinalis under different sexes [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because the option of reference genes varies drastically, insects of the same species, in terms of insect morphology, developmental stage, temperature, sex, and diet conditions, suggest that there is also no absolute generality between benchmark genes for the same species [ 29 , 30 , 31 , 32 ] . For instance, PGK and RPL13 are acceptable internal housekeeping genes in Cnaphalocrocis medinalis under different sexes [ 31 ]. PGK and EF1α are stable housekeeping genes expressed in Cnaphalocrocis medinalis larvae under different temperature conditions [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with our findings, other studies have shown that RPS11 expression is stable across various developmental stages in Tuta absoluta but is the lowest in diverse adult tissues [ 41 ]. In Cnaphalocrocis medinalis , RPL13 emerges as the most stable ribosomal protein across different adult ages but becomes the most unstable one in larval tissues and in larvae under temperature treatments [ 42 ]. These investigations suggest that the expression of ribosomal proteins varies significantly under different experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The seeds of three rice varieties, YY1540 (Ningbo Seed Co., Ltd, Ningbo, China), XS134, and ZZ39 (Zhejiang Wuwangnong Seeds Shareholding Co., Ltd, Hangzhou, China), were soaked for 24 h and drained, and then covered with moist gauze to induce germination for 48 h (Zhao et al 2022 ). They were planted in a white plastic bowl (26 cm × 17 cm × 8 cm in length, width, and height) to raise seedlings and transferred to flower pots (diameter 12 cm) after 12 d. All three varieties were planted in the greenhouse at Zhejiang Academy of Agricultural Sciences in Hangzhou, China (30.31° N, 120.20° E), and were used for experiments 40 d after transplantation.…”
Section: Methodsmentioning
confidence: 99%